Chicken soup for the soul : the gift of Christmas : a special collection of joyful holiday stories - Canfield, Jack, 1944-; Hansen, Mark Victor; Newmark, Amy. (Cos Cob, CT : Chicken Soup for the Soul Pub., 2012)
A collection of true personal stories about Christmas and the holiday season. Stories range from serious to thoughtful to heartwarming to funny.
All I want for Christmas -- Love actually -- Close encounters of the Santa kind -- Deck the halls -- It's a wonderful life -- A few good elves -- I'll be home for Christmas -- Toy story -- There will be family -- A Christmas carol -- Good gift hunting -- The Star of Bethlehem.
Originally published as a proprietary ed. in hardcover in 2010.
Keywords: Christmas -- Literary collections; Christmas -- Anecdotes